Creating effective sales and marketing relationships - Le Meunier-FitzHugh, Kenneth. (Selling and sales management collection., 2015)
The aim of this book is to discuss how corporate sales and marketing functions can operate collaboratively. Although effective sales and marketing interactions are critical to achieving organizational goals, their practical working relationship is frequently described as being unsatisfactory. Sales and marketing have developing their own perceptions of what should be achieved and how it can be realized. Because of the differences that exist between sales and marketing, the exploration of the issues and possible solutions to the sales and marketing dilemma offers an exciting opportunity for practitioners and academics, both in the context of management, and training and development programs, to deliver superior customer value. We will explore how sales and marketing can become more competitive in the face of dynamic and borderless markets, where lead generation is less important than building long-term relationships with customers. The book considers the follow areas related to the sales and marketing interface: How the crises in the sales and marketing interface became established. How alignment between sales and marketing can be achieved in lead generation. Consideration of the formal and informal methods of communication that can assist in establishing inter-functional collaboration. How collaboration between sales and marketing can improve customer relationships. The role of senior management in improving sales and marketing working relationships, and the optimization of the sales and marketing interface.